Dryopteridaceae, Lomariopsidaceae e Polypodiaceae em fragmentos florestais da microrregião de Altamira (Pará-Brasil) - SOUZA, Thaís Santos (2022)
This study is a survey of species of the Dryopteridaceae, Lomariopsidaceae and Polypodiaceae families occurring in forest fragments of the Altamira Microregion in the state of Pará, Brazil. The present study focused on four localities located in the municipalities of: Brasil Novo, Medicilândia and Vitória do Xingu; belonging to the Southwest Pará Mesoregion and the Altamira Microregion. In Brasil Novo the collections took place in the Planaltina Cave (Xingu Roots Ecological Site), Medicilândia in the Limoeiro Cave (Mino Trevisan Farm), Vitória do Xingu: Balneario Cantinho do Cipó Ambé and Vitória do Xingu Waterfall. For analysis and taxonomic identification of the collected specimens, usual techniques and specialized literature were used. Twenty-five individuals and 10 species were recorded in the area, including: Dryopteridaceae family with three species, Bolbitis serratifolia Schott, Cyclodium meniscioides C. Presl., Elaphoglossum luridum (Fée) H. Christ .; Family Lomariopsidaceae with two species, Nephrolepis cordifolia (L.) C. Presl., Nephrolepis rivularis (Vahl)) Mett ex Krug; and Family Polypodiaceae with five species, Campyloneurum phyllitidis (L.) C. Presl., Campyloneurum repens (Aubl.) C. Presl, Microgramma nana (Liebm.) T.E. Almeida, Microgramma reptans (Cav.) A.R. Sm, Phlebodium decumanum (Willd.) J. Sm.